2013
DOI: 10.1007/s00508-013-0349-8
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular morphology and function in patients with rheumatoid arthritis

Abstract: We conclude that TNF-alpha may be better marker of heart impairment caused by chronic inflammation in RA patients than NT-proBNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
2
15
0
8
Order By: Relevance
“…Both myocardial fibrosis and inflammation were associated with the disease activity. Thus, the chronic low-grade myocardial inflammation resulting in fibrosis may predispose RA patients to diastolic dysfunction that is common in RA and was confirmed by several echocardiographic studies [53][54][55]. Most studies demonstrated a significant inverse relationship between the E/A ratio and disease duration [54,56].…”
Section: Rheumatoid Arthritis and Heart Failurementioning
confidence: 90%
See 3 more Smart Citations
“…Both myocardial fibrosis and inflammation were associated with the disease activity. Thus, the chronic low-grade myocardial inflammation resulting in fibrosis may predispose RA patients to diastolic dysfunction that is common in RA and was confirmed by several echocardiographic studies [53][54][55]. Most studies demonstrated a significant inverse relationship between the E/A ratio and disease duration [54,56].…”
Section: Rheumatoid Arthritis and Heart Failurementioning
confidence: 90%
“…LV systolic dysfunction in RA was reported only in a few studies [55][56][57][58]. In the study of Bhatia et al, the prevalence of systolic dysfunction was three times more common as compared to general population [57].…”
Section: Rheumatoid Arthritis and Heart Failurementioning
confidence: 96%
See 2 more Smart Citations
“…RA patients seem to have significantly higher plasma NT-proBNP levels as compared with the general population [28], and in ERA, NT-proBNP levels have been found to be linearly associated with levels of CRP and demonstrated a strong graded relationship with CV outcomes [14,29]. Measurement of NT-proBNP has diagnostic and prognostic value in heart failure and other cardiovascular diseases [30,31].…”
Section: Discussionmentioning
confidence: 98%